(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
Based on the field studies and determination of the parameters of the stress-strain state, as well as the nature of the operation of reinforced concrete I-beam columns damaged during operation and during hostilities, a general method for determining the residual bearing capacity of elements was created. The article presents a method for determining the residual bearing capacity of damaged compressed reinforced concrete columns with damage at an angle, when the damage front is not parallel to one of the main axes of the section and the reinforcement of the steel cage. Prerequisites for the calculation of damaged reinforced concrete I-columns are proposed: the hypothesis of flat sections is accepted; stresses in the compressed zone are distributed uniformly with intensity ηf cd ; the stresses in the reinforcement are taken depending on the height of the compressed zone of concrete, the forces in the tension zone are perceived by the reinforcement and are accepted within the calculation of tension f t ; the work of tensioned concrete is not taken into account; the condition of parallelism of force planes is accepted (the plane of action of external and internal forces coincide or are parallel, depending on the design case); the reduced bearing capacity of exposed reinforcing bars is taken into account; damage front is a straight line. Reinforcement clip branches are taken into account as additional reinforcement. Equilibrium equations are composed. The proposals set forth in the article are based on the main provisions of the current norms and expand the scope of their use. The proposed method for determining the residual bearing capacity of reinforced concrete compressed elements of the tee profile, damaged during operation and reinforced with a steel cage, is statistically justified and reliable. This allows the calculation method to determine the possibility of further trouble-free operation of structures. A system of equations has been created that takes into account all the variety of shapes and sizes of the cross section of the element as a whole, the shapes and sizes of the compressed concrete zone. The reliability of these proposals is confirmed by comparison with data obtained experimentally, and statistical processing of such a comparison. The deviation variation coefficient is 0,125.